Active but not inactive granulomatosis with polyangiitis is associated with decreased and phenotypically and functionally altered CD56dim natural killer cells - Merkt, Wolfgang; Blank, Norbert; Hundemer, Michael; Lorenz, Hanns-Martin (Arthritis Research & Therapy, 2016)
The role of natural killer (NK) cells in granulomatosis with polyangiitis (GPA) is poorly understood. We recently reported that peripheral blood NK cell percentages correlate with the suppression of GPA activity (cohort I). The purpose of the current study was to further characterize NK cell subsets, phenotype and function in a second GPA cohort (cohort II).
Gesehen am 22.12.2017